Empowering Primary School Science Education: The Impact of LMS-Integrated E-Worksheets on Conceptual Understanding and Learning Outcomes - Sisri Wahyuni; Romi Kurniawan; Riri Marfilinda (Jurnal Penelitian Pendidikan IPA, 2026)
This study developed and evaluated Learning Management System (LMS)-integrated e-worksheets to enhance fifth-grade students' self-efficacy and conceptual understanding in science education. Using a Research and Development approach with the ADDIE model, the instructional material underwent expert validation, practicality assessment, and effectiveness testing. Validation results demonstrated high content and media validity (90.75%), while practicality scores from teachers and students reached 91%. Implementation significantly improved students' self-efficacy (95.5%) and conceptual understanding, with paired t-tests revealing statistically significant pre-post gains (p < 0.001). The findings indicate that purposefully designed LMS-integrated e-worksheets can effectively support blended learning environments, fostering both cognitive mastery and psychological empowerment in young learners. This research provides evidence-based guidance for integrating accessible digital platforms into elementary science instruction to create more student-centered and effective learning experiences.